Analysis of mathematics students’ mathematical thinking based on learning styles - Muhammad 'Azmi Nuha; Jun Mark R. Panlaan (UNION : Jurnal Ilmiah Pendidikan Matematika, 2026)
Mathematical thinking is an essential competence for mathematics students and involves four main components: generalizing, specializing, conjecturing, and justification or persuasion. A preliminary study conducted among undergraduate students of the Tadris Mathematics Study Program at UIN Saizu Purwokerto in 2024 indicated that students still experienced difficulties in formulating mathematical conjectures. Since learning styles may influence students’ engagement with mathematical tasks, this study aimed to explore prospective mathematics teachers’ learning styles and their mathematical thinking abilities. This study employed a qualitative methodology using a grounded theory approach. The research was conducted in 2025 at UIN Prof. K.H. Saifuddin Zuhri Purwokerto, involving students from the Mathematics Department. Data were collected through a learning style questionnaire, a mathematical thinking ability test, and interviews. The data were analyzed through reduction, presentation, conclusion drawing, and coding procedures. The results showed that the students’ learning styles were distributed as follows: visual 36%, auditory 32%, kinesthetic 16%, visual-auditory 8%, visual-kinesthetic 4%, and auditory-kinesthetic 4%. However, no specific pattern or tendency was found between learning styles and mathematical thinking ability. Several forms of mathematical thinking emerged from the data, including sequencing patterns without formulating conjectures, justifying processes through image manipulation, justifying processes by analyzing numerical relationships, errors in formulating mathematical conjectures, the importance of persuasion in validating conjectures, difficulties in understanding mathematically related problems, and the role of social media in supporting mathematical thinking. This study contributes to the literature by showing that prospective mathematics teachers’ mathematical thinking cannot be inferred directly from learning-style categories, but should be examined through the specific processes of conjecturing, justification, and persuasion demonstrated in mathematical problem solving.